The Measure of Machiavelli? Fear, Love, Hatred, and Trump. (December 2019) - Brunello, Anthony R.
The rise of populist leaders like Trump certainly raises issues of leadership and effectiveness. The current populist moment may be one of "Cultural Backlash, " but there is also merit in resurrecting and assessing the work of Niccolò Machiavelli in evaluating Trump's leadership and success. Would Machiavelli, with his emphasis on a "success ethic" and a studied moral indifference, rate Trump to be a "great prince?" This article analyzes Machiavelli's role and contemporary relevance as well as what he might say about a leader like Donald Trump. Machiavelli offers one insight into a style of leader that exposes the dangers of ignorance allied with self-interest in a nationalist pose. Also, we can visualize (with Machiavelli's help) a modern reconsideration of the dimensions of love, hate, and fear in 21st century leadership—especially among national populist leaders. This matters politically to us all.